ESCORRENT~ A SUPERFICIAL EN LAS VERTIENTES DE UNA CUENCA HIDROGRÁFICA EN EL ECOSISTEMA DEHESA. CUENCA DE GUADALPERAL~ N (Geographicalia, 1997)
In a sinall catchrnent under tlie deliesa landuse system overland flow production on slopes is investigated. The obtained results show tliat tl-ie determination of tl-ie tlireshold value for tl-ie generation of runoff is complex. Total precipitation and rnaxim~~m intensity in 10 minutes are the principal factors that explain tl-ie production and generatioii of slope runoff